Chitosan-based delivery of CRISPR-Cas9 plasmid in breast cancer stem cells - EKENTOK ATICI, CEYDA; ÖZBAŞ, SUNA (My University, 2023)
© 2023 Marmara University Press.Clustered regularly interspaced short palindromic repeat (CRISPR)-associated Cas9 nuclease system (CRISPR/Cas9) has emerged as a powerful toolbox for cancer therapy, serving as a gene fixed-point knock-out method. However, suitable gene carrier systems are urgently needed to encapsulate the CRISPR/Cas9 system and to improve the uptake into the cancer cells for anti-cancer therapy. In cancer therapy, breast cancer stem cells should be also targeted besides tumor cells. In this study, we prepared chitosan/CRISPR-Cas9/protamine nanoplexes and performed in vitro characterization. The results showed that the chitosan/protamine complex increased the zeta potential of the VEGF CRISPR/Cas9 plasmid from negative to positive. In vitro cell culture studies showed that VEGF silencing efficiency was 46.19% and 30.2% in MCF-7 and MCF-7s, respectively, after 7 days. The invasion capacity of cancer cells decreased significantly for both cell types. The results indicate that chitosan/VEGF CRISPR/Cas9 plasmid/protamine complexes can be used to reduce VEGF expression, leading to a decrease in the invasion capacity of breast cancer as well as breast cancer stem cells and providing proof of concept for more advanced studies, including in vivo studies, of this system.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); breast cancer; breast cancer stem cells; chitosan/protamine; CRISPR-Cas9; VEGF